Innovation and performance implications of customer-orientation across different business strategy types - Amonrat Thoumrungroje; Olimpia C. Racela (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Given that the ultimate goal of business is performance enhancement, this study approaches the phenomenon by drawing on resource-advantage (R-A) theory to conceptualize a model with the aim of investigating the links among composite operant resources (CORs), namely customer orientation, basic operant resources (BORs), innovative capability, and financial performance across Miles and Snow's five business strategy types, including prospectors, differentiated defenders, low-cost (LC) defenders, analyzers, and reactors. The scope of this study is firms based in the emerging market of Thailand. A final sample of 395 Thai firms participated in the self-administered survey. Multiple-group structural equation modeling and multivariate analysis of variance (MANOVA) were utilized to test the hypotheses. The results revealed insightful findings that advance the strategy and innovation literature. While business strategy types moderate the proposed relationships, the only one that is uniform across all five types of firms is the positive, strong, and significant customer orientation-innovation capability link. Moreover, customer orientation and innovative capability contribute significantly to financial performance among prospectors and LC defenders. However, only the former is essential to differentiated defenders, analyzers, and reactors. Overall, the findings suggest that managers must pay attention to connections between their chosen business-level strategy, customer-focused resources, and innovation capabilities to generate the best financial performance outcomes for their firms.
Keywords: 650; customer-relating; customer-response; financial performance; innovation capability; market-sensing; multiple group analysis; resource-advantage theory